A development of support technology for visually impaired swimmers towards Tokyo 2020 Paralympic Games - Ohgi, Y.; Narita, K.; Tanigawa, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
After the decision to host the Olympic and Paralympic Games in Tokyo in 2020, the Japanese Government consolidated para-sport under the jurisdiction of the Ministry of Health, Labour and Welfare (MHLW) into the Sports Agency under the Ministry of Education, Culture, Sports, Science and Technology (MEXT), and the Sports Agency now has jurisdiction over both the Olympic and Paralympic Games in Japan. As part of this, the High Performance Support Project Paralympic Research and Development for the Para swimmers was conducted under the Sports Agency with an eye on the 2016 Rio de Janeiro Paralympic Games. This research and development project started with a surveillance study in 2014 and continued as the development project until 2016. The authors were responsible for the development of training equipment and systems for use by visually impaired swimmers and coaches in training. Development continued after the Rio de Janeiro Paralympics until the postponed Tokyo Paralympics in 2021. This paper describes the development of technology to support visually impaired swimmers that the authors were responsible for.